0043 Circadian Rhythm of Energy Expenditure and Substrate Utilization During Constant Routine Conditions. (12th April 2019) - Morton, Sarah J; Rynders, Corey A; Tussey, Emma; Bessesen, Daniel H; Wright, Kenneth P; Broussard, Josiane L
Abstract: Introduction: Findings from previous studies indicate daily variation in energy expenditure (EE) depends on circadian phase in humans, though findings have been inconsistent. Changes in energy expenditure throughout the day and night during non-fasting conditions are important to understand factors influencing energy metabolism. The aim of this study was to determine the circadian rhythm of resting EE, respiratory quotient (RQ), and substrate utilization using a constant routine protocol. Methods: Six healthy adults (3F, age 27.7±2.2 years, BMI 24.7±3.2; mean±SD) participated in a 26-hour constant routine study following 1 week of outpatient monitoring. Subjects arrived at the laboratory in the evening and were provided an 8-hour sleep opportunity. After waking at their habitual time, participants remained in constant conditions, which included dim light (<8 lux), constant posture (bed rest), ambient temperature, and consumed small identical hourly meals. Melatonin was measured from hourly saliva and EE was measured every 3 hours using hood indirect calorimetry. EE data were aligned to dim light melatonin onset (DLMO). Results: Average DLMO occurred at 20:10h (± 18min). EE began to decline before DLMO and was lowest early in the biological night. RQ and carbohydrate oxidation (CHO-ox) were highest during the biological day, began to decline before DLMO, and remained lower throughout the biological night. In contrast, fat oxidation (FAT-ox) was highest close to DLMO. Conclusion: Previous findings show nadirs of EE, RQ, and CHO-ox close to the core body temperature minimum, which occurs during the middle of the biological night. In contrast, our constant routine study found lowest EE, RQ, and CHO-ox earlier in the biological night. However, current and prior assessments cannot determine precise nadir timing due to the relatively low frequency of sampling. Non-fasting studies with more frequent sampling of EE and substrate utilization are needed to determine how circadian timing impacts energy metabolism. Support (If Any): This work was supported by the Colorado Nutrition Obesity Research Center P30 DK048520-21, K01DK113063 to CR, K01DK110138 to JLB, and a University of Colorado Vice Chancellor of Research Innovative Seed Grant to JLB.